2010
DOI: 10.1073/pnas.1006496107
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan blocks oligodendrocyte progenitor maturation and remyelination through TLR2

Abstract: Failure of remyelination is largely responsible for sustained neurologic symptoms in multiple sclerosis (MS). MS lesions contain hyaluronan deposits that inhibit oligodendrocyte precursor cell (OPC) maturation. However, the mechanism behind this inhibition is unclear. We report here that Toll-like receptor 2 (TLR2) is expressed by oligodendrocytes and is up-regulated in MS lesions. Pathogenderived TLR2 agonists, but not agonists for other TLRs, inhibit OPC maturation in vitro. Hyaluronan-mediated inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
305
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(331 citation statements)
references
References 32 publications
15
305
5
1
Order By: Relevance
“…We2, 4 and others5 also previously reported that the PH20 hyaluronidase is elevated in demyelinating white matter lesions as well as oligodendrocyte progenitor cells. PH20 was also reported to be present, albeit at low levels, in the rat brain in a study on traumatic brain injury 6.…”
mentioning
confidence: 57%
“…We2, 4 and others5 also previously reported that the PH20 hyaluronidase is elevated in demyelinating white matter lesions as well as oligodendrocyte progenitor cells. PH20 was also reported to be present, albeit at low levels, in the rat brain in a study on traumatic brain injury 6.…”
mentioning
confidence: 57%
“…High molecular weight hyaluronan can directly inhibit OPC differentiation in culture. A recent study has found that hyaluronan inhibits OPC differentiation by binding to toll-like receptor 2 (TLR2) in oligodendrocyte lineage cells in culture and that hyaluronidases produced by OPCs convert high molecular weight hyaluronan to the more inhibitory low molecular weight form [46]. Moreover, inhibition of TLR2 and its signaling pathways can block hyaluronan inhibition to enable OPC differentiation.…”
Section: Hyaluronanmentioning
confidence: 99%
“…Several studies suggest that hyaluronan may have proinflammatory roles in the context of CNS autoimmunity: 1) it accumulates in demyelinated CNS lesions in MS and EAE (5,6); 2) HA production by dendritic cells and T-cells promotes antigen presentation and enhances T-cell activation and proliferation (2,3,7,8); 3) HA-CD44 interactions at the CNS vascular endothelium facilitate lymphocyte binding to vessels and CNS infiltration (9 -11); and 4) hyaluronan fragments signal through both Toll-like receptors (TLR) 2 and 4 and thereby stimulate inflammatory gene expression in immune cells (12).…”
mentioning
confidence: 99%